Study On Correlation Between Glycated Heamoglobin And Oxidative Stress In Diabetics - APARNA.R.R,; SUNEEL.B,; DR.SOWJANYA.B,; BALAKRISHNA.D, (International Journal of Pharma and Bio Sciences, 2012)
Oxidative stress plays an important role in the pathogenesis of diabetic complications. Hyper glycemia causes increased production of free radicals & evidence supports a prominent role for these reactive molecules as mediators of endothelial cell dysfunction in diabetes. Increased oxidative stress and impaired antioxidant defense have been suggested as contributory factors for initiation and progression of complications in diabetes mellitus. This study was conducted to evaluate the role of glyclosylation in causing oxidative stress. Study includes 50 known diabetic subjects. HbA1c, Thiobarbituric acid reactive substances, Total and oxidized ascorbic acid levels were estimated in diabetic subjects & controls. Raised HbA1c levels (p 0.005) in diabetic subjects shows increased glycation of proteins causing increased release of free radicals. Decreased levels of reduced ascorbic acid(p 0.01) are because of its consumption in antioxidant function. Thus the study out lines the role of HbA1c as an oxidant in DM & points that ascorbic acid is an antioxidant.